Existence of Prosecutors' Authority in Investigating Criminal Acts of Corruption Based on Law Number 31 of 1999 as Amended by Law Number 20 of 2001 concerning Eradication of Corruption - Rustam HS Akili (Budapest International Research and Critics University, 2022)
The main problems studied are as follows: Why in Indonesia, in the process of investigating criminal acts of corruption can be carried out by various law enforcement institutions, namely the Police, the Prosecutor's Office, to the KPK? And how is the existence of the Prosecutor's Office in investigating corruption based on Law Number 16 of 2004 in conjunction with Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 in conjunction with Law Number 30 of 2002? This research is a normative legal research, which is descriptive in nature, using a normative juridical approach, which is an approach through literature review with secondary data as the main source, which is obtained through data collection techniques with literature review, which is supported by interviews. After the data is collected, it is then analyzed in a normative-qualitative manner. The results of the study obtained answers, as follows: The process of investigating criminal acts of corruption in Indonesia can be carried out by law enforcement institutions, namely the Police, the Prosecutor's Office, to the KPK, because of the division of authority to investigate criminal acts of corruption, if the crime of corruption involves law enforcement, state administrators and other people who are related to criminal acts of corruption and receive attention that disturbs the public and/or involves state losses of at least Rp. 1,000,000,000.-.